2017
DOI: 10.3892/etm.2017.5538
|View full text |Cite
|
Sign up to set email alerts
|

Smoking increases the risk of diabetic foot amputation: A meta-analysis

Abstract: Abstract. Accumulating evidence suggests that smoking is associated with diabetic foot amputation. However, the currently available results are inconsistent and controversial. Therefore, the present study performed a meta-analysis to systematically review the association between smoking and diabetic foot amputation and to investigate the risk factors of diabetic foot amputation. Public databases, including PubMed and Embase, were searched prior to 29th February 2016. The heterogeneity was assessed using the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 40 publications
7
34
1
4
Order By: Relevance
“…This finding is consistent with studies that have demonstrated smoking as a risk factor in diabetic foot amputation. [10][11][12] Our study also confirmed that complications of diabetes mellitus ranked highest as the commonest indications for lower extremity amputation, followed by peripheral vascular disease. Similar trends were seen in studies conducted on major amputation.…”
Section: Discussionsupporting
confidence: 80%
“…This finding is consistent with studies that have demonstrated smoking as a risk factor in diabetic foot amputation. [10][11][12] Our study also confirmed that complications of diabetes mellitus ranked highest as the commonest indications for lower extremity amputation, followed by peripheral vascular disease. Similar trends were seen in studies conducted on major amputation.…”
Section: Discussionsupporting
confidence: 80%
“…This study showed that smoking patients had a higher DFU frequency than non-smoking patients (30.7% vs. 10.3%) and the odds of DFU occurrence were 3.8 times higher in smoking diabetic patients than in non-smoking patients. It is well established that serious factors play an important role in developing DFU, such as decreased blood flow in extremities, peripheral angiopathy, and peripheral neu- ropathy, that are more common in smokers (13,25,26). Furthermore, some studies have reported that smoking aggravates glucose hemostasis and accelerates the onset and progress of microvascular and microvascular diabetes complications (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, most of the subjects were female in the range of 40-60 years old. Based on gender, the female had three to seven times the risk of DM compared to male [7,8] due to the lipid level in female (20-25%) was higher than male (15-20%). Previous studies also found an association between gender and diabetes mellitus [4,9].…”
Section: Diabetes Mellitusmentioning
confidence: 99%